Role of GCR2 in transcriptional activation of yeast glycolytic genes. - Uemura, H (1992)
The Saccharomyces cerevisiae GCR2 gene affects expression of most of the glycolytic genes. We report the nucleotide sequence of GCR2, which can potentially encode a 58,061-Da protein. There is a small cluster of asparagines near the center and a C-terminal region that would be highly charged but overall neutral. Fairly homologous regions were found between Gcr2 and Gcr1 proteins. To test potential interactions, the genetic method of S. Fields and O. Song (Nature [London] 340:245-246, 1989), which uses protein fusions of candidate gene products with, respectively, the N-terminal DNA-binding domain of Gal4 and the C-terminal activation domain II, assessing restoration of Gal4 function, was used. In a delta gal4 delta gal80 strain, double transformation by plasmids containing, respectively, a Gal4 (transcription-activating region)/Gcr1 fusion and a Gal4 (DNA-binding domain)/Gcr2 fusion activated lacZ expression from an integrated GAL1/lacZ fusion, indicating reconstitution of functional Gal4 through the interaction of Gcr1 and Gcr2 proteins. The Gal4 (transcription-activating region)/Gcr1 fusion protein alone complemented the defects of both gcr1 and gcr2 strains. Furthermore, a Rap1/Gcr2 fusion protein partially complemented the defects of gcr1 strains. These results suggest that Gcr2 has transcriptional activation activity and that the GCR1 and GCR2 gene products function together.